1992
DOI: 10.1080/03079459208418816
|View full text |Cite
|
Sign up to set email alerts
|

Location of the amino acid differences in the S1 spike glycoprotein subunit of closely related serotypes of infectious bronchitis virus

Abstract: SUMMARYFour UK strains of three different serotypes were found to differ by only 2-3% of their S1 amino acids. The S1 sequences were also very similar to those of three Dutch isolates (D207, D274 and D3896), the greatest difference between two of the seven isolates being 4.4%. The few amino acid differences between the seven isolates were located largely between residues 19-122 and 251-347 of the mature S1 subunit.The seven isolates could be differentiated using 16 monoclonal antibodies in an enzymelinked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
2
7

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(234 citation statements)
references
References 27 publications
8
217
2
7
Order By: Relevance
“…In this study, PRV from cross-challenge studies were found to have a higher degree of correlation with amino acid identity values derived from partial S1 gene analysis (0.72) than ARV calculated from VN tests (0.61) ( Table 8). The S1 of IBV encodes epitopes important in VN (Cavanagh et al ., 1992) and protective immunity (Cavanagh et al ., 1997) in the chicken. Cavanagh et al (1997) examined the association of S1 sequence with protective immunity in their efforts to determine whether the S1 subunit was the major inducer of immunity in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PRV from cross-challenge studies were found to have a higher degree of correlation with amino acid identity values derived from partial S1 gene analysis (0.72) than ARV calculated from VN tests (0.61) ( Table 8). The S1 of IBV encodes epitopes important in VN (Cavanagh et al ., 1992) and protective immunity (Cavanagh et al ., 1997) in the chicken. Cavanagh et al (1997) examined the association of S1 sequence with protective immunity in their efforts to determine whether the S1 subunit was the major inducer of immunity in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…However, the IBV genome consists of single-stranded RNA with a high mutation frequency. Molecular studies with IBV have shown that new IBV serotypes and genotypes can emerge as a result of only a very few changes or mutations in the amino acid sequence of the spike gene, while the majority of the virus remains unaltered (Cavanagh et al, 1992b;Cavanagh, 1995). Additionally, several workers demonstrated (Kottier et al, 1995) or provided circumstantial evidence Kusters et al, 1989Kusters et al, , 1990Zwaagstra et al, 1992;Cavanagh et al, 1992a;Wang et al, 1993Wang et al, , 1994Jia et al, 1995) that IBV can undergo recombination during mixed infections.…”
Section: Strain Classificationmentioning
confidence: 99%
“…Antigen ELISAs have been reported as a successful confirmation test for detecting IBV antigen in allantoic fluid of inoculated eggs (Yagyu & Ohta, 1987;Hesselink et al, 1988;Nagano et al, 1990;Koch et al, 1991b;Cavanagh et al, 1992b;Ignjatovic & Ashton, 1996). This technique can be especially useful when many samples have to be tested.…”
Section: Detection Of Ibv Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibody analysis has revealed that most of the antigenic sites of virus-neutralization antibody-inducing epitopes are formed by a few amino acids that occur in the first quarters of the S1 subunit, especially in the hyper-variable regions (HVR) [2,9,10]. Hence, classification by genotype has been done on the basis of the antigenic site, especially for HVR, on the S gene [15,16].…”
mentioning
confidence: 99%